Towards Communication Channels That Enlighten - Sumartono . (Communication Sphere, 2015)
ABSTRACTStudy on the channel of political communication (media) boils down to two thingsnamely, accuracy of channels selection, and utilization of existing channels. This understandingis important and affect the success of political activity that will be executed. Usually the failure ofthe political influence the choice of a constituent is not only caused by the Communicator ormessages to be delivered but also on political communication or media channels. In otherwords, political communication channel component is as important as the existence of a politicalCommunicator. This means that errors in choosing political influential communication channelssignificantly to selection or selectivity of society.Keywords: Channels, Political Communications, Enlighten